Does Financial Resource Development Effort Affect the Dynamic Entrepreneurial Capability and Performance of SMEs? - Mangifera, Liana; Perwithosuci, Winny; Aisyah, Siti; Widawati, Mega Wahyu (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
The changes and uncertainty of the business environment in the VUCA era are serious challenges that must be faced, especially for SMEs. The unpreparedness of business actors to face these changes can impact the decline in SME performance and business sustainability. SMEs must continue to adapt to all changes that occur in their capabilities. Thus, SME players must have a business strategy using their resources by increasing dynamic entrepreneurial capabilities supported by financial resources to compete in the market. This research aims to analyze the relationship between digital technology capability, relational capability, innovation capability, financial resource development, and SMEs’ performance in Surakarta. The results of 120 SME respondents in Surakarta show that dynamic entrepreneurial capability, in this case, is measured using the variables digital technology capability (DTC), relational capability (RC), and innovation capability (IC) which are proven to have a significant influence on SMEs performance and also the development of financial resources can only partially mediate digital technology capability, however Financial resource development cannot mediate the influence of relational capability or innovation capability on SMEs performance. This research implies that it is important for SMEs to have dynamic entrepreneurial capabilities and develop their financial resources to maintain and improve their business performance.